CHARACTERISTICS OF ATTENTION AND BEHAVIOR IN YOUNG SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2025)
This article aims to study the characteristics of attention in young school students and changes in their development. Since young children are not able to educate and manage attention, their attention characteristics are often specific and often change. The study aims to analyze how the main types of attention (activity, constancy, strength and distribution of attention) are manifested in young children, as well as what changes occur in these characteristics depending on age.